Estudo dos ventos no Rio Grande do Sul e simulação para um ciclone extratropical usando o Modelo MM5 - Pereira, Ana Carolina Cardoso (2008)
In this work a study of the winds in Rio Grande do Sul, during the period 2000-2007 is presented to identify where and when the wind were stronger in the State. The wind data obtained at 10m height, at three time observation (00, 12 and 18UTC) of 15 meteorological stations, well distributed in the State are utilized. The identification of the stations where the winds were stronger and with less spectrum of variation was made using a Weibull distribution to the monthly average values of velocity, calculated on the total period of data from each station (between 4 and 8 years) and for time. The similarity of velocities behavior between the stations with 8 years of data was obtained by applying the method K-means, non-hierarchical clustering technique, setting up 4 groups for homogeneous regions of pentad average velocities in the state, by hour of observation. Sensibility tests with two Planetary Boundary Layer (PBL) parameterizations (Blackadar and MRF) of MM5 model were realized by using two nested grids with 35 sigma levels in vertical, centered in Rio Grande do Sul and with initial and contour data from NCEP (1º resolution in latitude and longitude). The validation of simulated versus observed velocities at 10m height was realized with the calculation of bias error, the mean square root of error and standard deviation of errors. The cities of São Luiz Gonzaga and Santa Vitória do Palmar stood out from the others because they had more often high values of k and c parameters. The homogeneous group, characterized by having the highest values of pentadal avegared velocities was constitued predominantly by the stations of Santa Vitória do Palmar (in the extreme south of the state) and Passo Fundo (located in the northern region). The highest velocities were observed in the month of November, in Santa Vitória do Palmar. The selected case study was the extratropical cyclone that struck the southern Rio Grande do Sul in the period from 9 to November 13, 2002. The errors between observed and simulated velocities in both experiments were relatively large. The comparison between results and observed data in some stations showed that Blackadar PBL parameterization was better than MRF parameterization.